THE CREDIT RESTRUCTURING AS A FORM OF PROTECTION AGAINST CUSTOMERS DURING THE COVID-19 PANDEMIC - Agustina, Rani Sri (UNISSULA, 2021)
The submission of credit restructuring during the covid pandemic is a form of legal protection for customers who have difficulty paying credit. The COVID-19 stimulus policy in the banking sector was issued after observing developments in the economic impact related to the spread of COVID-19, which is still continuing globally and domestically. The approach method used is empirical juridical. The results of the research obtained stated that debtors who were affected by COVID-19, including micro, small and medium business debtors, were having difficulty fulfilling their obligations to banks, because the debtor or debtor's business was affected by the spread of COVID-19 either directly or indirectly to the economy. So far it has been running efficiently according to the restructuring agreement. The customer pays according to the agreement that has been made. Credit restructuring to maintain credit quality, which saves from bad credit.